A Comprehensive Exploration of Bioluminescence Systems, Mechanisms, and Advanced Assays for Versatile Applications - Asiri N. Dunuweera; Shashiprabha P. Dunuweera; K. Ranganathan (Biochemistry Research International)
Bioluminescence has been a fascinating natural phenomenon of light emission from living creatures. It happens when the enzyme luciferase facilitates the oxidation of luciferin, resulting in the creation of an excited-state species that emits light. Although there are many bioluminescent systems, few have been identified. D-luciferin-dependent systems, coelenterazine-dependent systems, Cypridina luciferin-based systems, tetrapyrrole-based luciferins, bacterial bioluminescent systems, and fungal bioluminescent systems are natural bioluminescent systems. Since different bioluminescence systems, such as various combinations of luciferin-luciferase pair reactions, have different light emission wavelengths, they benefit industrial applications such as drug discovery, protein-protein interactions, in vivo imaging in small animals, and controlling neurons. Due to the expression of luciferase and easy permeation of luciferin into most cells and tissues, bioluminescence assays are applied nowadays with modern technologies in most cell and tissue types. It is a versatile technique in a variety of biomedical research. Furthermore, there are some investigated blue-sky research projects, such as bioluminescent plants and lamps. This review article is mainly based on the theory of diverse bioluminescence systems and their past, present, and future applications.